2017
DOI: 10.1177/0145445517692081
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Implementation of Skill Acquisition Programs by Special Education Teachers and Staff for Students With Autism Spectrum Disorder

Abstract: The present investigation examined special education teachers' selection and use of teaching strategies for receptive identification training with children with autism spectrum disorder (ASD) in their classrooms. Teachers first responded to a survey in which they provided examples of receptive identification tasks taught in their classrooms, rated the efficacy of teaching strategies, described how they determined whether skills were mastered, listed any assessments they conducted to identify relevant prerequis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 18 publications
(27 reference statements)
0
34
0
Order By: Relevance
“…Several descriptive studies reported that treatment‐integrity errors occur during instruction with consumers of applied behavior analysis (e.g., children with ASD; Brand et al, 2017; Breeman et al, 2020; Carroll et al, 2013; Kodak et al, 2018), but we cannot say whether the type and degree of errors evaluated in this translational study are likely to affect the acquisition of consumers like children with ASD in a similar way. Once additional studies have replicated our findings, future researchers should consider employing a parametric analysis of treatment integrity errors with individuals who are receiving behavior‐analytic skill‐acquisition intervention.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Several descriptive studies reported that treatment‐integrity errors occur during instruction with consumers of applied behavior analysis (e.g., children with ASD; Brand et al, 2017; Breeman et al, 2020; Carroll et al, 2013; Kodak et al, 2018), but we cannot say whether the type and degree of errors evaluated in this translational study are likely to affect the acquisition of consumers like children with ASD in a similar way. Once additional studies have replicated our findings, future researchers should consider employing a parametric analysis of treatment integrity errors with individuals who are receiving behavior‐analytic skill‐acquisition intervention.…”
Section: Discussionmentioning
confidence: 79%
“…Descriptive research has suggested that treatment integrity errors occur in applied contexts (Breeman et al, 2020; Carroll et al, 2013; Kodak et al, 2018), and some studies on the effects of reduced treatment integrity took place in similar applied settings (e.g., Breeman et al, 2020; Carroll et al, 2013; Holcombe et al, 1994; Noell et al, 2002). However, another option is to conduct studies within a human operant laboratory (e.g., Bergmann et al, 2017; St. Peter Pipkin et al, 2010) and adopt a translational approach (Mace & Critchfield, 2010) to evaluate the effects of integrity errors on learning.…”
mentioning
confidence: 99%
“…Special education teachers may be aware of effective instructional methods such as observing others who are implementing ABA strategies, reviewing case studies, watching and reflecting on videotapes, listening to lectures, and receiving feedback, and collecting data (Khaleel, 2019) but they still need a guide and foundation to start with (Alotaibi, 2015;Khaleel, 2019). However, educators may fail to implement some of ABA practices correctly such as consistently implementing trial-based instruction teaching (Kodak, Cariveau, LeBlanc, Mahon & Carroll, 2018). Unfortunately, there are few ABA experts in Saudi Arabia, which impacts implementation of effective behavioral instructional practices (CFAR, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Auditory–visual conditional discrimination (AVCD) training is ubiquitous in early intervention and special education services for learners with autism spectrum disorder (ASD; Grow & LeBlanc, 2013; Kodak et al, 2018; Leaf & McEachin, 1999; Lovaas, 2003). For example, learners are taught to select pictures of common items (e.g., food, clothing, animals, vehicles) given an auditory sample stimulus of the spoken word (e.g., “cat”) or environmental sound (e.g., cat meowing) that corresponds to the picture.…”
mentioning
confidence: 99%